A zinc Schiff base complex as high‐efficiency stabilizer for flexible poly(vinyl chloride) against thermal degradation. Issue 2 (25th January 2021) - Fu, Zhimin; Yang, Zhanhong; Rong, Yao; Deng, Lie; Wu, Jian
Abstract: A high‐efficiency zinc chelate stabilizer, Zn‐(2‐hydroxybenzylidene) aspartic acid (Zn‐HBAPA), has been synthesized. From dehydrochlorination and discoloration tests conducted at 180°C, Zn‐HBAPA has shown to be an excellent thermal stabilizer for flexible poly(vinyl chloride) (PVC) when compared with industrially used cadmium‐zinc soap stabilizer. Blending CaSt2 derivatives and costabilizer THAM (tris[hydroxymethyl]aminomethane) with synthesized Zn‐HBAPA stabilizer in different ratios substantially improved the thermal stability of PVC while maintaining the initial color of the PVC. The thermal stability time and the induction time were 55.5 and 52 min, respectively. The initial color of PVC samples held for more than 70 min, and the time to turn the PVC samples completely black took 160 min. Results also showed that not only did the Zn‐HBAPA stabilizer show a good synergistic effect when combined with CaSt2 and THAM, but it also exhibited good compatibility with PVC. Abstract :